2012
DOI: 10.1007/s13277-012-0333-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of transforming growth factor beta (TGF-β) signaling axis molecules and E-cadherin in colorectal cancer

Abstract: The transforming growth factor beta (TGF-β) signaling pathway has been considered both a tumor suppressor and a cancer promoter. Additionally, downregulation of cell adhesion molecules such as E-cadherin plays an important role in the metastatic potential of colorectal cancer (CRC). The aim of the present study was to evaluate TGF-β, TGF-β type I receptor (TGF-βR1), TGF-β type II receptor (TGF-βR2), Smad4, pSmad2/3, and E-cadherin expression in colorectal carcinoma and to correlate the obtained data with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 40 publications
4
33
0
1
Order By: Relevance
“…Several of the studies suggested that the expression of TGF-β1 was also associated with decreased patient survival, which was consistent with previous findings [8,9]. The expression of TGF-βR2 [8,18] and Smad4 [8,20] was reported to be associated with increased patient survival in some reports. Hence, it appears that there is a certain trend to the findings.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Several of the studies suggested that the expression of TGF-β1 was also associated with decreased patient survival, which was consistent with previous findings [8,9]. The expression of TGF-βR2 [8,18] and Smad4 [8,20] was reported to be associated with increased patient survival in some reports. Hence, it appears that there is a certain trend to the findings.…”
Section: Discussionsupporting
confidence: 86%
“…These studies have similar findings in some respects. The expression of TGF-β1 was generally associated with poor prognostic features including high-grade histology, advanced T-stage, lymph node metastasis and distant metastases [8,18,19]. Several of the studies suggested that the expression of TGF-β1 was also associated with decreased patient survival, which was consistent with previous findings [8,9].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations